2000
DOI: 10.1053/jhep.2000.18713
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycans Initiate Dengue Virus Infection of Hepatocytes

Abstract: The clinical pictures caused by the arthropod-borne dengue viruses (DEN), which belong to the family of Flaviviridae, vary from a simple febrile fatigue to severe hemorrhagic fever and the often rapidly fatal dengue shock syndrome. 1 Consistent with a worldwide escalation of infection rates during the last decade, the more severe manifestations are occurring in an increasing proportion of cases. 2 Although DEN infections are a particular threat in tropical and subtropical regions, endemic transmission has rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(159 citation statements)
references
References 49 publications
10
148
0
1
Order By: Relevance
“…Because CXCL10 is the predominant CXCR3 ligand induced by DENV infection (17,26,28) but was not critical for recruitment of effector cells, we examined other potential antiviral mechanisms. Previously, we demonstrated that CXCL10 inhibits DENV entry into hepatocytes by competing with DENV for binding to the cell surface heparan sulfate (31), a coreceptor for DENV entry (44)(45)(46). In the current study, we demonstrated that CXCL10 also competes with DENV for binding to heparan sulfate on the surface of neurons, thus preventing DENV entry and reducing infectivity.…”
Section: Discussionsupporting
confidence: 58%
“…Because CXCL10 is the predominant CXCR3 ligand induced by DENV infection (17,26,28) but was not critical for recruitment of effector cells, we examined other potential antiviral mechanisms. Previously, we demonstrated that CXCL10 inhibits DENV entry into hepatocytes by competing with DENV for binding to the cell surface heparan sulfate (31), a coreceptor for DENV entry (44)(45)(46). In the current study, we demonstrated that CXCL10 also competes with DENV for binding to heparan sulfate on the surface of neurons, thus preventing DENV entry and reducing infectivity.…”
Section: Discussionsupporting
confidence: 58%
“…Infectivity of certain viruses including AAV2 is inhibited in the presence of soluble heparin (Summerford and Samulski, 1998;Dechecchi et al, 2000;Hilgard and Stockert, 2000). Presumably, heparin attaches to heparinbinding sites on the viral particle, directly blocking infection.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs) and other attachment factors The first molecule that was identified to participate in DENV entry into mammalian cells was heparan sulfate [20][21][22]. Highly sulfated GAGs are ubiquitous molecules present on the surface of several types of cells, also mediating attachment for many viruses [23].…”
Section: Dengue Virus Receptors In Human Cellsmentioning
confidence: 99%